Local Government Forestry Expenditure and Forest Land Cover: A Preliminary Lesson from Decentralized Indonesia - Firda Hidayati; Yogi Vidyattama; Cameron Gordon (Economics and Finance in Indonesia, 2016)
Even though government of Indonesia invests billions of rupiah to tackle deforestation, its effectiveness has been questionable. This study analyses changes in rates of forest cover in Indonesia and their association with forestry expenditures (FE) spent by the provincial governments. Based on 2007 to 2010 data, linear multiple regression results indicate that FE is not enough to tackle the negative change in forest land cover that could represent deforestation. Moreover, it was found that FE have negative association with forest land cover and therefore, can be associated to deforestation. This negative association remains when other factors that affect forest land cover such as wood extraction, agriculture outcome, forestry outcome, population growth and population density and initial environmental conditions have been controlled.AbstrakWalaupun pemerintah Indonesia telah menginvestasikan trilyunan rupiah untuk mengurangi deforestasi, akan tetapi efektifitasnya dipertanyakan. Penelitian ini menganalisa tingkat perubahan luasan tutupan hutan di Indonesia and asosiasinya dengan Pengeluaran Sektor Kehutanan (PSK) yang dibelanjakan oleh pemerintah provinsi. Berdasar data tahun 2007 sampai 2010, hasil regresi multiple linier mengindikasikan bahwa PSK tidak cukup untuk mengurangi akibat negatif dalam perubahan hutan dan lahan yang dapat mngakibatkan deforestasi. Lebih lanjut, ditemukan bahwa PSK berhubungan erat pengurangan luasan hutan, yang dapat dikaitkan dengan deforestasi. Asososiasi yang negatif ini tetap terjadi walaupun faktor lain yang memengaruhi tutupan hutan seperti penebangan kayu, hasil pertanian, hasil kehutanan, pertumbuhan populasi dan kepadatan populasi dan kondisi awal lingkungan telah dikontrol.Kata kunci: Deforestasi, Hutan Tropis; Populasi Penduduk; Tutupan Hutan; Pengeluaran untuk Reboisasi HutanJEL classifications: E62; Q58; H76